A 0.5 V quasi-floating gate self-cascode DTMOS current-mode precision full-wave rectifier - Mitwong, Hanphon; Kasemsuwan, Varakorn (My University, 2012)
This paper presents a 0.5 V quasi-floating gate self-cascode DTMOS current-mode precision full-wave rectifiers (PFWR). The circuit is designed based on improved Wilson current mirrors. All MOS transistors are biased on the edge of conduction, enabling the circuit to operate at low voltage with low power consumption. Negative feedback mechanism of the Wilson current mirror and cross coupling techniques have been employed to reduce the input impedance. Spectre is used to perform the simulation and the results show the frequency of operation as high as 100 MHz using a standard 0.13 μm CMOS technology. The mismatch between the input and rectifier's output is 0.24% for an input current of ±100 μA. The DC transfer characteristic shows good linearity, very sharp corner at zero crossing point and good symmetry during positive and negative input cycle, while power dissipation is 570 nW © 2012 IEEE.
Keywords: full-wave; low power; low voltage; rectifier